Suffering Exhausted Life Like Burning at Both Ends of a Candle - Women With Menopausal Fatigue (International Journal of Studies in Nursing, 2020)
Background: Fatigue is a common complaints for perimenopausal or menopausal women. It is a subjective feeling and deeply affect women's lives. Studies evaluating it as a marker for diseases or the transition of menopause among menopausal women are lacking. Aims: To explore the life experiences among women with menopausal fatigue. Methods: In- depth interview were conducted with 17 Taiwanese women with a mean age of 52.2years, who perceived themselves as getting tired or exhausted life but have no major or serious diseases were invited by in-depth interviewed. Data were analyzed by constant comparative method. Results: “Suffering exhausted life like burning at both ends of a candle” was the core category for describing and guiding the process of women with menopausal fatigue. During this process, “Energy Exhaustion” was identified as the antecedent condition. Once the woman became aware, she would begin the process of “Suffering exhausted life like burning at both ends of a candle”. This process would be marked by action and interaction among the categories of “Need refreshing or diverting attention”, “Seeking family or significance others help and supports”, and “Arranging leisure activities and exercise”. Throughout this process women viewed their fatigue life by acceptance by “Slowing and modifying my life paces” or retrieval it but felt frustration and recycling the process of Energy Exhaustion. Conclusion: Menopausal fatigue was viewed as suffering exhausted life like burning at both ends of a candle instead of a silent life message. It is like menopausal symptoms needing to attention.